Identification of Zakat Institution Risks and Mitigation Efforts to Increase Operational Effectiveness (Case Study of LAZISMU Daerah Istimewa Yogyakarta) - Dona Amalia Priasih; Yuni Humaira; Alma Zahwa Kirana (Nusantara: Journal of Cultural Research, 2025)
This study analyzes the operational effectiveness of the Muhammadiyah Zakat, Infaq, and Sadaqah Institution (LAZISMU) of the Special Region of Yogyakarta through a risk identification approach and mitigation strategies. The problems raised include performance barriers such as delays in fund distribution, program inconsistencies, and recording errors that disrupt internal efficiency. The study uses a descriptive quantitative approach with data collection techniques through structured interviews with internal staff. Risk analysis was carried out using a score assessment method (frequency × impact), both before and after the implementation of mitigation. The results showed a significant decrease in the operational, strategic, reputational, compliance, and market risk categories after the intervention. The mitigation strategies implemented include human resource training, digitization of data management systems, increasing transparency of reports, and updating standard operating procedures (SOPs). These findings confirm that structured risk management can significantly improve the operational effectiveness of zakat institutions and strengthen organizational governance that is responsive and adaptive to external dynamics.